Evaluation of Immunostimulatory Potential of Branded and US-Generic Enoxaparins in an In Vitro Human Immune System Model. (April 2015) - Luna, Ernesto; Agrawal, Pankaj; Mehta, Riyaz; Vernhes, Charlotte; Viskov, Christian; Amiral, Jean; Warren, William L.; Drake, Donald R.
Low-molecular-weight heparins (LMWHs) have several positive therapeutic effects and can also form immunostimulatory complexes with plasma proteins, such as platelet factor 4 (PF4). We compared the innate response and functional profiles of branded and US-generic enoxaparins from 2 manufacturers in either native or PF4-bound forms in an in vitro model of human immunity. In an analysis of 2 product lots from each manufacturer and multiple separate batches of protein–heparin complexes, branded enoxaparin was shown to be consistently nonstimulatory for innate responses, whereas US-generic enoxaparins generated variable immunostimulatory profiles depending on the enoxaparin lot used to prepare the PF4–LMWH complexes. Production of tissue factor pathway inhibitor (TFPI), a physiologic heparin-induced inhibitor of tissue factor-induced coagulation that was used as a functional readout of biological activity of enoxaparins in these assays, was heightened in the presence of branded enoxaparin complexes, but its levels were variable in cultures treated with complexes containing US-generic enoxaparins. Analytical analyses suggest that the heightened immunostimulatory potential of some of the US-generic enoxaparin product lots could be tied to their capacity to form ultra-large and/or more stable complexes with PF4 than the other LMWHs included in this study. Although these distinct biological and analytical profiles might be related to the composition and/or consistency of branded and US-generic enoxaparins included in our data set, further studies are warranted to elucidate the pathophysiological relevance of these in vitro findings.